Electrospinning of continuous aligning yarns with a `Funnel' target - Afifi, A.M.; Nakano, S.; Yamane, H.; Kimura, Y. (John Wiley & Sons, 2010)
A new electrospinning set-up is described for continuous aligning of poly(L-lactide) yarn. It comprises a slowly rotating grounded `funnel' target and a winder placed right up to the funnel. A charged polymer jet is ejected from a nozzle. The electrospun fibers are first accumulated on the mouth plane of the funnel to form a web. The web is then pulled upward and guided to a winder on which twisted fibers are continuously wound as a bundle. Each filament of the bundle is slanted at about 45 relative to the collecting direction, and its average diameter is 6.0+/-1.9 mu m. The drawn fiber shows improved tensile properties as a result of the increased molecular orientation. The morphologies of the twisted fibers before and after drawing are compared.